2020
DOI: 10.1038/s41598-020-59044-w
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shock index multiplied by Glasgow Coma Scale (rSIG) predicts mortality in severe trauma patients with head injury

Abstract: The reverse shock index (rSI), a ratio of systolic blood pressure (SBP) to heart rate (HR), is used to identify prognosis in trauma patients. Multiplying rSI by Glasgow Coma Scale (rSIG) can possibly predict better in-hospital mortality in patients with trauma. However, rSIG has never been used to evaluate the mortality risk in adult severe trauma patients (injury Severity Score [iSS] ≥ 16) with head injury (head Abbreviated injury Scale [AiS] ≥ 2) in the emergency department (ED). This retrospective case cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
0
33
1
Order By: Relevance
“…7 A new scoring tool, rSIG, which is defined as the reverse shock index (the SBP divided by HR) multiplied by the Glasgow Coma Scale (GCS) score, has been shown to be more predictive of in-hospital mortality than standard scoring systems, including SI, among adult patients. [8][9][10] Reverse shock index multiplied by Glasgow Coma Scale has recently been shown to be more predictive of mortality than SIPA in both military and civilian settings. 11,12 This suggests that rSIG may be more generalizable than SIPA to pediatric trauma patients regardless of injury mechanism; however, its full utility is unstudied in the pediatric population.…”
mentioning
confidence: 99%
“…7 A new scoring tool, rSIG, which is defined as the reverse shock index (the SBP divided by HR) multiplied by the Glasgow Coma Scale (GCS) score, has been shown to be more predictive of in-hospital mortality than standard scoring systems, including SI, among adult patients. [8][9][10] Reverse shock index multiplied by Glasgow Coma Scale has recently been shown to be more predictive of mortality than SIPA in both military and civilian settings. 11,12 This suggests that rSIG may be more generalizable than SIPA to pediatric trauma patients regardless of injury mechanism; however, its full utility is unstudied in the pediatric population.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that the GCS score was related to the mortality of patients with TBI [3,22]. In a study by Han et al, a GCS score of ≤5 was associated with mortality in most groups, and the GCS score of non-survivors was 4 (3)(4)(5)(6)(7)(8)(9) in this study [22]. In another study on patients with TBI, the OR of the GCS score for mortality was 0.765, similar to that obtained in the present study [3], in which the GCS score of nonsurvivors corresponded to the unresponsiveness parameter in the AVPU scale [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several triage tools for TBI have been developed, and studies have reported the efficacies of these tools for predicting prognosis [3][4][5][6][7][8]. Among these, the Injury Severity Score (ISS) and Revised Trauma Score (RTS) are the most commonly used tools in severe trauma patients, including those with TBI [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low GCS on arrival, high international normalized ratio (INR), and the need for intubation were all found to be risk factors of in-hospital mortality even though multivariate analysis failed to identify them as independent predictors of death [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%